Authorship and type specimens of Alburnoides kubanicus (Teleostei: Cyprinidae) - Šanda, Radek; Mlíkovský, Jiří (Zootaxa, 2012)
Boguckaâ & Coad (2009: 138) recognized Alburnoides kubanicus as a valid species in the genus Alburnoides Jeitteles (1861: 325), attributing it to Berg (1932a). We show below that Berg (1932a) did not describe the species and discuss the proper authorship of the name.